Thymoquinone β-Cyclodextrin Nanoparticles System: A Preliminary Study. Issue 5 (11th July 2012) - Cardoso Cardoso, T. T.; Galhano Galhano, C. I. C. C. I. C.; Ferreira Marques Ferreira Marques, M. F. M. F.; Moreira da Silva Moreira da Silva, A. A.
Abstract : Thymoquinone is a natural product, the main constituent of Nigella sativa seeds, which exhibits anti-inflammatory and anticancer activities. Among several existing molecules capable of forming an inclusion compound structure, cyclodextrins are applied in the pharmaceutical industry either to increase solubility of hydrophobic molecules or to protect molecules from inactivation or degradation. β -Cyclodextrin is currently the most common cyclodextrin in pharmaceutical formulations and probably the best studied in humans. In order to study the properties of inclusion compounds based on cyclodextrins and thymoquinone Fourier Transform Infrared (FTIR), Ultraviolet-Visible, Positron Annihilation Lifetime (PAL) Spectroscopies and calorimetric studies by Differential Scanning Calorimetry (DSC) were used. The obtained results indicate the formation of a 1 : 1 inclusion compound between cyclodextrin and thymoquinone. PALS and DSC measurements also provided evidence of the inclusion compound's activity.